Development of a Practical Synthesis of 4-[6-(Morpholinomethyl)-pyridin-3-yl]naphthalen-1-amine, a Key Intermediate for the Synthesis of BIRB 1017, a Potent p38 MAP Kinase Inhibitor - Lu, Bruce Z.; Li, Guisheng; Rodriguez, Sonia; Liu, Jianxu; Eriksson, Magnus C.; Tan, Zhulin; Song, Jinhua J.; Yee, Nathan K.; Farina, Vittorio; Senanayake, Chris H. (Synlett, 2013)
The development of synthetic routes to 4-[6-(morpholinomethyl)pyridin-3-yl]naphthalen-1-amine, the key intermediate of p38 MAP kinase inhibitor BIRB 1017, via (1) trialkylmagnesium ate complex mediated metalation and borylation followed by Suzuki coupling reactions and (2) pyridine-ring formation from a vinamidinium salt, is described.
Keywords: metalation; cross-coupling; tandem reaction; boron; magnesium